School Climate and Teachers’ Commitment: A Case Study of Malaysia - Yusof, Najeemah M. (International Journal of Economics, Business and Management Studies, 2012)
The purpose of this study was to analyze the relationships, between school climate and teachers’ commitment. The study investigates the predictability of key dimensions of school climate in related to collegial leadership, professional teacher behaviour, achievement press and institutional vulnerability towards teacher commitment. The population of this study consisted of teachers from 5 National Primary Schools [NPS] in the Island of Penang, Malaysia. Quantitative data was collected using two [Organisational Climate Index (OCI) and Teachers Organisational Commitment (TOC)] adopted instruments which were modified to form the Questionnaire for this study and its validity and reliability was established. The data were analyzed to determine the overall openness of school climate in selected National primary schools in Penang, Malaysia and to find out the commitment level of their teachers. The study found that the level of school climate openness and overall teachers’ commitment of the selected 5 primary school is high. As for correlation between school climate dimensions, the result shows that there is a positive correlation with teachers’ commitment. The regression analysis showed that only professional teacher behaviour made a significant contribution to teachers’ commitment.